2018
DOI: 10.1111/liv.13872
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and risk of hepatocellular carcinoma in patients with type 2 diabetes

Abstract: Metformin was associated with a reduced risk of HCC in a dose-response pattern. Users of both metformin and aspirin or metformin and statin had the lowest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 24 publications
7
67
0
2
Order By: Relevance
“…A pivotal, population‐based cohort study including 10 309 patients with T2DM observed a significantly decreased cancer‐related mortality for metformin compared to sulphonylurea and insulin . These results have been validated in the context of HCC within several, large observational studies including up to 97 430 patients with HCC demonstrating a reduced HCC for metformin users when compared to diabetic and/or non‐diabetic controls . Finally, two meta‐analyses summarizing 10 and 13 studies reported a 50% reduction of HCC incidence among up to 481 358 participants including 240,678 patients with HCC .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A pivotal, population‐based cohort study including 10 309 patients with T2DM observed a significantly decreased cancer‐related mortality for metformin compared to sulphonylurea and insulin . These results have been validated in the context of HCC within several, large observational studies including up to 97 430 patients with HCC demonstrating a reduced HCC for metformin users when compared to diabetic and/or non‐diabetic controls . Finally, two meta‐analyses summarizing 10 and 13 studies reported a 50% reduction of HCC incidence among up to 481 358 participants including 240,678 patients with HCC .…”
Section: Discussionmentioning
confidence: 82%
“…40 These results have been validated in the context of HCC within several, large observational studies including up to 97 430 patients with HCC demonstrating a reduced HCC for metformin users when compared to diabetic and/or non-diabetic controls. [8][9][10]41 Finally, two meta-analyses summarizing 10 and 13 studies reported a 50% reduction of HCC incidence among up to 481 358 participants including 240,678 patients with HCC. 11,12 These convincing results have led to the acknowledgement of HCC risk reduction by metformin within the current German practice guideline.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one study reported a positive association only in NASH cirrhotic patients, and not in other aetiologies such as alcohol use and viral hepatitis . Metformin use has also been associated with decreased risk of cancers, including HCC in diabetic patients . A recently published meta‐analysis, including 10 studies reporting 22 650 cases of hepatocellular carcinoma in 334 307 patients with type 2 diabetes, showed a 50% reduction in hepatocellular carcinoma incidence with metformin use .…”
Section: Introductionmentioning
confidence: 99%
“…19 Metformin use has also been associated with decreased risk of cancers, including HCC in diabetic patients. [22][23][24][25] A recently published meta-analysis, including 10 studies reporting 22 650 cases of hepatocellular carcinoma in 334 307 patients with type 2 diabetes, showed a 50% reduction in hepatocellular carcinoma incidence with metformin use. 24 Another recent large, population-based, casecontrol study using the Taiwanese National Health Insurance Research Database reported that, among diabetic patients, metformin users had a 21% lower risk of hepatocellular carcinoma after adjusting by several confounders including the presence of cirrhosis and different aetiologies of chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin is well known for its anti-diabetic role [26]. It was also shown that metformin reduced the risk of cancer in patients with T2DM [27,28]. The role of metformin in suppressing the proliferation of GC cells is related to its role in blocking cell cycles, which could explain why metformin decreased tumour size in mice with xenograft GC tissues [29,30].…”
Section: Discussionmentioning
confidence: 99%